Pengertian Teologis Gereja Berdasarkan Kitab-Kitab Taurat dan Implementasinya untuk Masa Kini - Agustinus Djali; Daya, Maswati (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract: Since the church was founded, it has been faced with problems. The fathers have triedto lay the foundation of church teachings very fundamentally, but until today it seems that theproblems have not disappeared, instead there are deviations in both doctrine and service thatopen up gaps for misguidance and cause church growth to stagnate. Therefore, the churchshould immediately introspect and return to its basic principles, namely "building a churchbased on the Bible, both the Old and New Testaments." The church in the time of Moses wasan ancient church that was built by God in the beginning, it should be an example and rolemodel for the church today. The purpose of this study: First: to study the nature of the churchbased on the books of the Torah so that today's congregation can have a theologicalunderstanding of churching so that they can apply it in their lives and congregational services.Second: to emphasize that the teachings about the true Church are also found in the books ofthe Torah, not only in the books of the New Testament. Third: to try to implement thetheological understanding of the church based on the books of the Torah for today so that thecongregation continues to strive to improve its teaching and performance in churching. Thiscan be done through Theological Schools and seminars, sermons, and Bible studies, and cellgroups in local churches.Keywords: Church of the Torah, Implementation.Abstrak: Sejak gereja berdiri terus diperhadapkan dengan masalah. Para bapa telah berusahameletakkan fondasi ajaran gereja dengan sangat fundamental, namun sampai pada hari ini punnampaknya masalah belum juga sirna, sebaliknya muncul penyelewengan baik dalam doktrinmapun pelayanannya yang membuka celah bagi penyesatan dan mengakibatkan pertumbuhangereja mengalami stagnant. Maka gereja hendaklah segera mengintrospeksi diri serta kembalikepada azas dasarnya yakni “membangun gereja berdasarkan pada Alkitab baik PL maupunPB”Gereja pada jaman Musa merupakan gereja purba yang telah dibangun oleh Allah padamulanya, seharusnya menjadi contoh dan teladan bagi gereja pada masa kini. Tujuan penelitianini : Pertama: untuk mempelajari hakikat gereja berdasarkan kitab-kitab Taurat agar jemaatmasa kini dapat memiliki suatu pemahaman teologis tentang bergereja sehingga dapatmengaplikasikannya dalam kehidupan dan pelayanan berjemaat. Kedua: untuk menegaskanbahwa ajaran tentang Gereja yang benar juga terdapat dalam kitab-kitab Taurat, bukan hanyapada kitab-kitab P B. Ketiga: berupaya mengimplementasikan pengertian teologis gerejaberdasarkan kitab-kitab Taurat untuk masa kini sehingga jemaat terus berupaya meningkatkan,pengajaran dan kinerjanya dalam bergereja. Hal ini dapat dilaksanakan melalui Sekolah-Sekolah Teologi dan seminar-seminar, khotbah, serta penelahan Alkitab, komsel pada gerejalokal.Kata Kunci:Gereja kitab-kitab Taurat, Implementasi